Solid-state dewetting of silver-thin films: self-assembled nano-geometries. (7th December 2020) - Sultan, M T; Manolescu, A; Svavarsson, H G; Valfells, A
Abstract: The study presents the dynamics of solid-state dewetting of silver (Ag)-film annealed in N2 ambient, analyzed by atomic force microscopy and scanning electron microscopy. Varying the annealing parameters (i.e. temperature and time) and Ag-film thicknesses were taken into account, to determine their effect over the solid-state dewetting of Ag-films. Several morphological evolutions from nanohole to the presence of metastable nanorings were observed. It was determined that structures annealed at high temperature (≥900 °C) and/or time (≥2 h) results in formation of metastable nanorings and whose geometrical aspects and population grew with increasing film thickness. Possible applications of the structures for fabrication of silicon nanowire arrays and photo-emitters are briefly described.